Low handgrip strength levels among adolescents in a city in southern Brazil - Silva D.A.S. (2017)
© 2017 Elsevier LtdObjective To estimate the prevalence of low handgrip strength (HGS) levels and sociodemographic characteristics, health behaviours and body fatness status related in adolescents. Method Cross-sectional epidemiological study with 636 adolescents aged 14–19 years in a city in southern Brazil. HGS was measured by dynamometer. Sociodemographic and behavioural data were collected using self-report questionnaires. Body mass and height was measured by Body Mass Index. Results Prevalence of low HGS levels was 47% (63.5% boys, 37.7% girls). Boys aged 14–16 years were more likely to have low HGS levels. Girls who were of higher socioeconomic status and who were less physically active were more likely to have low HGS levels. Overweight girls were less likely to have low HGS levels. Conclusions High prevalence of low HGS levels was observed in adolescents. Increased HGS levels should be focused on younger boys and normal-weight girls with higher socioeconomic status and lower levels of physical activity.